Karakteristik Fisikokimia dan Organoleptik Gula Merah Cair Asal Pulau Kisar Provinsi Maluku - Yohanis, Abraham; Lawalata, Vita N; Tetelepta, Gilian (Tropical Small Island Agriculture Management, 2023)
This study aims to determine the best ratio of brown sugar to water in making liquid brown sugar based on its physicochemical and organoleptic properties. This study was designed using a completely randomized design (CRD). The ratio of brown sugar to water consists of 4 treatment levels: 1:1, 1:2, 1:3, and 1:4. The results showed that the brown sugar “water treatment of 1:1 is the best treatment with physicochemical characteristics such as moisture content of 48.29%, total sugar of 50.94%, total dissolved solids of 52.3, and pH of 5.3. Based on hedonic organoleptic characteristics for color 3.28 (like), aroma 3.44 (like), viscosity 2.8 (rather like), taste 3.52 (like), overall 3.52 (like), and for quality organoleptic characteristics hedonic, namely color 3.72 (brownish), aroma 3.48 (fragrant), viscosity 3.0 (thick), taste 3.44 (sweet) and overall 3.52 (like).